Transfer of Learning Outcomes from an English-for-Specific-Academic-Writing Course to Subject-Specific Courses - Kassab, Kalthoum (Journal of English Language Teaching and Applied Linguistics, 2021)
This study investigated the transfer of ten learning outcomes from an ESAP writing course to subject-specific courses. It was a longitudinal study carried over one academic year. It followed 40 undergraduate students of English under normal classroom conditions. A mixed-methods approach was used. It included analysis of students’ written exams from four subjects, student semi-structured interviews, and a student questionnaire. Elements from Barnett and Ceci’s (2002) transfer taxonomy were also used. They helped classify the targeted learning outcomes in terms of specificity/generality and helped distinguish between near and far transfer contexts. Results showed that the transfer of the ten learning outcomes to the near and far transfer contexts was affected by the specificity/generality of the learned skill in the first place. The learning outcomes that were classified as specific transferred more easily to both the near and far transfer contexts, while the more complex learning outcomes transferred in a constrained manner. The findings suggest that an ESAP writing course that is informed by teaching for transfer principles offers students a more authentic learning environment to hone their writing skills and to transfer these skills to other contexts. However, this transfer can be a very slow process.